Pengaruh Metode Blended Learning Berbantuan Aplikasi Chatbot Kana terhadap Hasil Belajar Peserta Didik Kelas V - Sumiati, Sumiati; Hermansyah, Hermansyah; Setyaningrum, Vidya (AS-SABIQUN, 2025)
Integrating technology into education is crucial for enhancing the learning system. However, in practice, teachers often fail to incorporate technology into their teaching methods to maximize students' active participation duriing the learning process. Many remain reliant on traditional lecture and question-and-answer formats. This study aims to examine the effects of applying a blended learning approach. supported by a chatbot application on students' learning outcomes. This study utilizes a quantitative approach with a quasi-experimental design, employing a pretest-posttest control group format. The study sample was made up of 108 students from three different classes, and the sample was randomly selected, comprising 73 students from classes A and B. The data collection methods included both test and non-test techniques, utilizing tools such as test questions, observation sheets, and documentation, all of which were validated and tested for reliability before the research began. The gathered data were analyzed using both descriptive statistics and inferential statistical methods. The findings of the study indicated that the control group had an average pretest score of 31.62, which increased to 54.05 in the posttest. Meanwhile, the experimental group had a pretest score of 45 and a posttest score of 76.94. Statistical testing indicated a significant effect of the blended learning method supported by the KANA chatbot application, with a value of 8.5230. In conclusion, the application of the blended learning approach with the support of the KANA chatbot application has a substantial positive influence on students' learning outcomes.